Loopography Examination For Colon Cancer Cases In Tangerang District Public Hospital - Gando Sari; Triana Retno Putri; Samsun Samsun; Sriyatun Sriyatun; Nursama Heru Apriantoro (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2019)
Loopography examination technique is a radiological examination technique in lower digestive tract (colon) by inserting a positive contrast media into the colon through an artificial hole in abdominal area. This examination aims to evaluate the anatomy and physiology function from distal section of colon to anus with ca colon clinical. This research was conducted in radiology installation of Tangerang District General Hospital during November to December 2018, using a qualitative descriptive method with a literature study approach and interview. The results found that loopography examination in Tangerang District General Hospital did not require special preparation. The kind of contrast media used is a water-soluble contrast media such as iohexol with a ratio of 1: 3 mixed with NaCl. This loopography contrast media can be inserted through the clean stoma or anal. The routine projections performed for loopography examination in Tangerang District General Hospital are Plan photos of Abdomen, Antero Posterior (AP) and Lateral. But sometimes Oblique projection is also used as an addition if is less obvious anatomy due to overlap/superposition.